PENGARUH KETERSEDIAAN KOLEKSI BUKU PERPUSTAKAAN TERHADAP MINAT BACA SISWA DI SDI AT-TAQWA PAMULANG - Zakia Nurhasanah; Muhammad Mamduh Nuruddin (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the effect of the availability of library book collections on students’ reading interest at SDIT At-Taqwa Pamulang in the 2025/2026 academic year. This research employed a quantitative approach with a non-experimental design using a survey method. The sample consisted of 42 students selected as respondents. Data were collected through questionnaires, observation, documentation, and interviews. Data analysis used simple linear regression to examine the relationship between the availability of library book collections (X) and students’ reading interest (Y).he results showed that the availability of library book collections was categorized as high, with a percentage of 79.25%, while students’ reading interest was also categorized as high, with a percentage of 66.22%. The regression analysis produced the equation Y = 44.687 + 0.131X, indicating a positive effect of the availability of library book collections on students’ reading interest. However, the coefficient of determination was 0.014, meaning that the effect was very low, contributing only 1.4%, while the remaining 98.6% was influenced by other factors not examined in this study. In conclusion, the availability of library book collections has a positive but low influence on students’ reading interest.